Neural Differentiation of Mouse Embryonic Stem Cells—An in vitro Approach to Profile DNA Methylation of Reprogramming Factor Sox2-SRR2 - Batool, Sajida; Kayani, Mahmood Akhtar; Valis, Martin; Kuca, Kamil (Frontiers in Genetics, 2021)
Sox2 is one of the core transcription factors maintaining the embryonic stem cells (ES) pluripotency and, also indispensable for cellular reprograming. However, limited data is available about the DNA methylation of pluripotency genes during lineage-specific differentiations. This study investigated the DNA methylation of Sox2 regulatory region 2 (SRR2) during directed differentiation of mouse ES into neural lineage. ES cells were first grown to form embryoid bodies in suspension which were then dissociated, and cultured in defined medium to promote neural differentiation. Typical neuronal morphology together with the up-regulation of Pax6, neuroepithelial stem cell intermediate filament and β-tubulin III and, down-regulation of pluripotency genes Oct4, Nanog and Sox2 showed the existence of neural phenotype in cells undergoing differentiation. Three CpGs in the core enhancer region of neural-specific SRR2 were individually investigated by direct DNA sequencing post-bisulfite treatment and, found to be unmethylated in differentiated cells at time-points chosen for analysis. This analysis does not limit the possibility of methylation at other CpG sites than those profiled here and/or transient methylation. Hence, similar analyses exploring the DNA methylation at other regions of the Sox2 gene could unravel the onset and transitions of epigenetic signatures influencing the outcome of differentiation pathways and neural development. The data presented here shows that in vitro neural differentiation of embryonic stem cells can be employed to study and characterize molecular regulatory mechanisms governing neurogenesis by applying diverse pharmacological and toxicological agents.